The birthright eaudiobook Song of acadia series, book 3. - Oke, Janette (Song of Acadia, 2012)
Best-selling inspirational authors Janette Oke and T. Davis Bunn have joined forces once again in the third book of the Song of Acadia series. Called back to England to assume her duty as the heir to an earldom, Nicole leaves Nova Scotia and everything she loves behind. Determined to be a proper lady, Nicole struggles with her position until her sister Anne visits. Anne quickly adapts to life in England, while Nicole longs for Nova Scotia. And beneath the surface is a dark secret threatening to separate these sisters forever.